Divine hyperbolics: Desmond, religion, metaphysics and the postmodern - Simpson, Christopher Ben (2008)
This thesis is a systematic presentation of William Desmond's philosophical system and an argument for its viability and superiority relative to dominant alternate visions, here represented by that of John D. Caputo. Desmond, I argue, provides a viable and preferable alternative to - and an alternative narrating of - the kind of late twentieth century "postmodern" anti-metaphysical frame represented by Caputo. Desmond's vision is viable in that it answers Caputo's critiques - showing that they need not be the case. Here Desmond shows how metaphysics (and ethics and religion informed by metaphysics) escapes Caputo's narration/location. Desmond defeats Caputo's defeaters in order to make Desmond's vision a possible position. On a deeper level, Desmond's vision is arguably preferable inasmuch it can be used to critique Caputo's vision - largely in that it (Desmond's vision) as it can be seen to fulfill Caputo's motivating concerns in a more satisfying manner than Caputo's own vision. It does this in two ways. First, from Desmond's vision one can see how such a "LeviNietzschean" vision tends to betray its own motivating concerns. Second, Desmond's position shows how a metaphysical vision/stance/picture (like Desmond's) is, in fact, necessary for one to fulfill these concerns (... or simply necessary, as such). In this manner, Desmond out-narrates the "postmodern" "LeviNietzschean" position, showing Desmond's as a preferable position - as possessing a broader and greater explanatory reach.